Fearlessness as an Underlying Mechanism Leading to Conduct Problems: Testing the INTERFEAR Model in a Community Sample in Spain - Kostas A. Fanti; Ioannis Mavrommatis; Beatriz Díaz-Vázquez; Laura López-Romero; Estrella Romero; María Álvarez-Voces; Olivier F. Colins; Henrik Andershed; Nicholas Thomson (MDPI AG, 2024)
Conduct problems (CP) in childhood and adolescence have a significant impact on the individual, family, and community. To improve treatment for CP, there is a need to improve the understanding of the developmental pathways leading to CP in boys and girls. Prior research has linked the child's fearlessness and callous-unemotional (CU) traits, as well as experiences of parental warmth and punitive parenting, to CP. However, few studies have tested the interplay of these factors in contributing to future CP development. The present study aimed to test the InterFear model, which suggests that fearlessness in early childhood leads to CP through an indirect pathway involving low positive parenting, high negative/punitive parenting, and callous-unemotional (CU) traits. The sample included 2467 Spanish children (48.1% girls; Mage = 4.25; SD = 0.91), followed up across a five-year period. Besides a direct association between fearlessness in early childhood and future CP, the results found an indirect pathway whereby fearlessness reduces positive parenting and increases punitive parenting, which contributes to the development of CU traits and sets the stage for CP in later childhood. The specific indirect effect from fearlessness to CP via CU traits accounted for most of the variance, suggesting the existence of a temperamental pathway independent of parental variables. Further, two additional indirect pathways, exclusive of fearlessness, were identified, which started with low parental warmth and positive parenting, leading to CP via CU traits. These findings support the InterFear model, demonstrating multiple pathways to CP with the involvement of fearlessness, parenting practices, and CU traits. This model might play a pivotal role in the development of targeted prevention and intervention strategies for CP.